2015
DOI: 10.1002/pbc.25750
|View full text |Cite
|
Sign up to set email alerts
|

Does Routine Imaging of Patients for Progression or Relapse Improve Survival in Rhabdomyosarcoma?

Abstract: Routine surveillance imaging practice should be critically reviewed for children with RMS. Although our findings must be validated by larger studies, they do have substantive implications. Reduced imaging tailored to the risk and pattern of recurrence, associated risks and cost could improve patient quality of life and decrease health-care expenditure without compromising outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…We also found that in addition to history/symptoms and UCats, MIBG scans detected the majority of recurrences. However, our study and several other reports of surveillance imaging for non‐NB pediatric cancers have not shown that early detection is associated with improved salvage rates or survival . Further support to decrease the use of CT specifically for pulmonary metastatic disease at recurrence was recently demonstrated in another single institution study.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…We also found that in addition to history/symptoms and UCats, MIBG scans detected the majority of recurrences. However, our study and several other reports of surveillance imaging for non‐NB pediatric cancers have not shown that early detection is associated with improved salvage rates or survival . Further support to decrease the use of CT specifically for pulmonary metastatic disease at recurrence was recently demonstrated in another single institution study.…”
Section: Discussionmentioning
confidence: 38%
“…However, our study and several other reports of surveillance imaging for non-NB pediatric cancers have not shown that early detection is associated with improved salvage rates or survival. [20][21][22]41 43,44 There are conflicting publications in pediatric patients with noncancer diagnoses demonstrating adverse events 45,46 leading to many recent commentaries and the formation of the Smart Tots (Strategies for Mitigating Anesthesia-Related Neurotoxicity) Advisory Committee. 18,45,46 Future trials may be needed to determine whether anesthesia may have adverse longterm neurodevelopmental sequelae in patients with pediatric cancer who receive many anesthetics/sedations for imaging and other procedures.…”
Section: Discussionmentioning
confidence: 99%
“…9,20 This study shows that the majority of patients with relapsed RMS experience clinical symptoms at the time of relapse (71.8%). The assumption is that surveillance imaging will lead to earlier detection of tumor relapse and subsequently to an improved prognosis after relapse.…”
Section: Discussionmentioning
confidence: 75%
“…[9][10][11] Furthermore, repetitive imaging is associated with substantial costs, could add additional radiation exposure, and often requires anesthesia. [9][10][11] Furthermore, repetitive imaging is associated with substantial costs, could add additional radiation exposure, and often requires anesthesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation